Analytical evaluation of Oldroyd-B nanoliquid under thermo-solutal Robin conditions and stratifications. (November 2020) - Waqas, M.; Hayat, T.; Alsaedi, A.; Khan, W.A.
Highlights: Mixed convection flow of Oldroyd-B nanoliquid is formulated. Hydromagnetic stratified flow is modeled and analyzed. Thermo-solutal convective conditions are considered. Homotopy analysis method is opted for computations. Abstract: Chilling systems are important in the improved technological thermal mechanisms which are considered continuously in passive along with active heat-transference improvement procedures. Engineers recommended several approaches to upsurge heat transference of thermal structures. The pulsating flow, corrugated tube, magnetic field aspect and nanoliquids are the heat-transference improvement procedures delved continuously. In present research work, we addressed the heat-transference characteristics of non-Newtonian (Oldroyd-B) liquid towards heated stratified surface. Thermally radiative laminar flow is modeled. In addition, we accounted Buongiorno's nanoliquid model which includes Brownian along with thermophoretic diffusions. Modeling is further based on heat source, magnetohydrodynamics, dual stratification, thermal radiation and convective conditions. Mathematical system is simplified through boundary-layer idea. Similarity variables are reported with the aim to simplify complex mathematical system. Homotopy algorithm yields convergent results of non-dimensional expressions. Our study unveils diminution of thermal along with solutal fields when stratification factors are increased.